2019
DOI: 10.3892/mmr.2019.10331
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of epigallocatechin‑3‑gallate against human oral squamous cell carcinoma through inhibition of cell proliferation and induction of apoptosis: In�vitro and in�vivo murine xenograft study

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common malignant tumors in the oral region. Despite current therapeutic strategies, the survival rate has not been improved for several decades. Thus, it is important to develop a novel approach for the treatment of OSCC. Epigallocatechin-3-gallate (EGCG) is a major constituent of green tea and has previously been demonstrated to inhibit the growth of several types of cancer cells. However, few studies have investigated the effect of EGCG on human OSCC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 29 publications
(43 reference statements)
1
25
0
2
Order By: Relevance
“…Oral and head and neck cancer cells exposed to green tea and epigallocatechin-3-gallate (EGCG), respectively, lead to a decrease in the expression of the phosphorylated epidermal growth factor receptor (EGFR), suggesting that catechins are potential cancer chemo-therapeutic or chemo-preventive agents [77,78]. In vitro, tea catechins promote a decrease in the proliferation of different human head and neck squamous cell carcinoma (HNSCC) cell lines [77][78][79][80][81][82]. Li et al [82] found that EGCG affects the proliferation, apoptosis, migration and invasion of tongue squamous cell carcinoma cells through the Hippo-TAZ signaling pathway.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral and head and neck cancer cells exposed to green tea and epigallocatechin-3-gallate (EGCG), respectively, lead to a decrease in the expression of the phosphorylated epidermal growth factor receptor (EGFR), suggesting that catechins are potential cancer chemo-therapeutic or chemo-preventive agents [77,78]. In vitro, tea catechins promote a decrease in the proliferation of different human head and neck squamous cell carcinoma (HNSCC) cell lines [77][78][79][80][81][82]. Li et al [82] found that EGCG affects the proliferation, apoptosis, migration and invasion of tongue squamous cell carcinoma cells through the Hippo-TAZ signaling pathway.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Moreover, polyphenols alone induce G0/G1 cell-cycle arrest and apoptosis [83]. EGCG also induces the G1 phase arrest of human OSCC cells [81]. Activation of the p53 tumor suppressor gene by green tea polyphenols could explain the induction of cell cycle arrest and apoptosis [84].…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…OSCC is a highly aggressive cancer with frequent local recurrences and lymph node metastases [4]. The overall 5-year survival rate for OSCC patients have not been improved and remained at approximately 50% for several decades [5]. Therefore, how a diagnostic/prognostic assessment of gene expression could be translated into better patient survival.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have also shown that drinking more than 10 cups of green tea per day reduces the risk and delays the onset of cancer compared to those who drink less than 3 cups per day. In addition, smokers taking green tea extract (2000-2500 mg/day) for 4 weeks reduced the DNA damage of oral keratinocytes [217,218].…”
Section: Green Tea Egcg Egc and Ecgmentioning
confidence: 99%